2003
DOI: 10.1097/00002371-200307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Vaccination for Patients With Melanoma and Other Types of Cancer Based on Pre-existing Peptide-Specific Cytotoxic T-Lymphocyte Precursors in the Periphery

Abstract: Identification of antigenic peptides expressed on cancer cells enables us to treat cancer patients with peptide-based immunotherapy. Although optimal protocols for peptide-based vaccines have not yet been elucidated, boosting the immune system could be a better approach than priming the immune system to elicit prompt and potent peptide-specific T-cell responses in cancer patients. With this possibility in mind, the authors undertook a clinical trial in which cancer patients were vaccinated with peptides (maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 20 publications
1
46
0
1
Order By: Relevance
“…However, the existence of tumor-reactive CD8 ϩ T cells in the peripheral circulation of a patient or an experimental animal is not sufficient to cause the rejection of an established tumor. Clinical trials using peptide Ags for vaccination succeeded in routinely generating tumor-reactive CTLs in patients (5,6), but vaccination alone only sporadically induced tumor regression in patients with metastatic disease. Even in transgenic mice that were engineered to enable every T cell to express a tumor-reactive TCR, tumors still grew progressively.…”
mentioning
confidence: 99%
“…However, the existence of tumor-reactive CD8 ϩ T cells in the peripheral circulation of a patient or an experimental animal is not sufficient to cause the rejection of an established tumor. Clinical trials using peptide Ags for vaccination succeeded in routinely generating tumor-reactive CTLs in patients (5,6), but vaccination alone only sporadically induced tumor regression in patients with metastatic disease. Even in transgenic mice that were engineered to enable every T cell to express a tumor-reactive TCR, tumors still grew progressively.…”
mentioning
confidence: 99%
“…In contrast, HLA-DRB1*0403-restricted CD4 ϩ T cell precursors against the UBE2V 43-51 peptide were detected only after the peptide vaccination. In our clinical trial, vaccination with four peptides, including the UBE2V 43-51 peptide, did not increase but rather abolished the pre-existing CTL precursors in the periphery in three HLA-A2 ϩ cancer patients (22), although the peptide vaccination induced UBE2V 43-51 peptide-specific IgG in these three patients. We have no explanation for the abolishment of peptide-specific CTL precursors in these patients, but we speculate that the concomitant induction of Th cells contributed to the increase in HLA-A2-restricted T cell response to the UBE2V peptide, at least in this particular patient.…”
Section: Discussionmentioning
confidence: 54%
“…This means that the dramatic induction of IgG reactive to administered peptides is not limited to the present case. In addition, peptide vaccination resulted in the induction of IgG reactive to several tumor peptides other than the UBE2V 43-51 peptide (22,23). This indicates that the elicitation of IgG reactive to administered peptides is not limited to the UBE2V 43-51 peptide.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This means that the PTHrP 102 -111 peptide was recognized by both the cellular and humoral immune systems. Although we do not yet have a clear understanding of the roles played by peptide-specific IgG in antitumour immune responses, our clinical trials revealed that a peptide vaccination frequently resulted in the induction of IgG reactive to the CTL epitope peptides which were administered Tanaka et al, 2003). In addition, the induction of IgG reactive to the vaccinated peptides was positively correlated with longer survival of advanced lung cancer patients .…”
Section: Discussionmentioning
confidence: 87%